2019
DOI: 10.1002/ecy.2825
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating adaptive, carry‐over, and plastic antipredator responses across a temporal gradient in Pacific chorus frogs

Abstract: The development of antipredator traits is dependent on the frequency and intensity of predator exposure over evolutionary and ecological time. We hypothesized that prey species would respond with increasing accuracy when exposed to predators across generational, ontogenetic, and immediate time scales. We assessed larval Pacific chorus frog (PSRE; Pseudacris regilla) individuals that varied in population sympatry, embryonic conditioning, and immediate exposure to stocked populations of rainbow trout (Oncorhynch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 80 publications
(140 reference statements)
1
9
0
Order By: Relevance
“…In this systematic review, we examined the relative frequencies and the extent that these important processes are studied in concert. While the effect of herbivores on plants have long been studied, and it has been well shown that herbivores can directly and indirectly impact plant reproduction, growth, and population dynamics (Hawkes & Sullivan, 2001;Ohgushi, 2005;Boivin, Doublet & Candau, 2019;Garcia & Eubanks, 2019), the small number of studies that were located within this review indicate how infrequently the effects of herbivores on pollination are studied. These studies were also heavily biased towards damage done by insects, temperate biomes, and the effects of a single herbivore species on a single plant species.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this systematic review, we examined the relative frequencies and the extent that these important processes are studied in concert. While the effect of herbivores on plants have long been studied, and it has been well shown that herbivores can directly and indirectly impact plant reproduction, growth, and population dynamics (Hawkes & Sullivan, 2001;Ohgushi, 2005;Boivin, Doublet & Candau, 2019;Garcia & Eubanks, 2019), the small number of studies that were located within this review indicate how infrequently the effects of herbivores on pollination are studied. These studies were also heavily biased towards damage done by insects, temperate biomes, and the effects of a single herbivore species on a single plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Complete florivory has been shown to have direct impacts on floral abundance. The net outcome of this form of direct damage is dependent on the strategy of the plant (Juenger & Bergelson, 1997;Wise, Cummins & De Young, 2008;Garcia & Eubanks, 2019). In some cases, plants will over-produce flowers as a defense against florivory creating more flowers than the plant is able to bring to seed (Huth & Pellmyr, 1997).…”
Section: Effects Of Florivory On Pollinationmentioning
confidence: 99%
See 3 more Smart Citations